Analisis Fatwa No. 23/DSN-MUI/III/2002 Tentang Potongan Pelunasan Pembiayaan Murabahah Sebelum Jatuh Tempo Dalam PerspektiF Al-URF - Angga Adigara; M Lathoif Ghozali (ITB AAS INDONESIA Surakarta, 2023)
This research aims to analyze Fatwa No. 23/DSN-MUI/III/2002 concerning early repayment discounts in Murabahah financing from the perspective of Al-URF. The main issues addressed in this study include the compatibility between Islamic finance principles and the concept of Al-URF, the influence of Al-URF on the interpretation and implementation of the fatwa, and the implications of Al-URF for Murabahah financing. The objective of this research is to investigate the impact of Al-URF on the understanding and practice of early repayment discounts as outlined in the fatwa. A mixed-method approach will be employed, combining qualitative and quantitative methods. The research will involve analyzing the fatwa, Islamic finance literature, case studies, and empirical data. The findings of this study are expected to contribute to the ongoing discourse on the integration of Islamic finance principles with contemporary financial practices, highlighting any discrepancies or gaps in the understanding and application of early repayment discounts in Murabahah financing from the perspective of Al-URF.